Development of a Socio-Cultural Value-Based Character Education Model for High School Students in the City of Ternate - Irwan Abdullah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Character education is an important issue in the development of education in Indonesia. This study aims to: (1) Identify the problems faced by teachers; (2) The determinants that cause “deviant behavior” among students; (3) developing an initial model of socio-cultural-based character education; (4) analyze the effectiveness of the educational model. The method used, Research Development. This research can show that teachers in the learning process are still lacking in exploring the social and cultural values ​​of the people of Ternate City. There are internal and external factors that cause deviant behavior among students. Based on these findings, a Character Education Model Based on Socio-cultural Values ​​has been developed. Development models have produced syllabus, lesson plans and lessons for Social Studies Teaching Materials. It is hoped that in the future similar relevant research will be carried out for the development of syllabus, lesson plans and teaching materials in schools in Ternate City